Socialism, Farming, and Resistance: How Cuban Socialism is Beating the Embargo - Dmitri Gourianov (Caribbean Studies Students' Union, 2023)
Beginning as a small assignment which ought to have taken two days, it soon ballooned into a three month project looking at the Cuban political system and the farming sector's role in developing not only Socialist theory, but Socialism in practice. As the collapse of Cuban Socialism has been expected for the past four decades by Western scholars and lawmakers, this very same inevitability has perplexed its proponents as it continues to not occur. Cuba has been under embargo by the United States for over sixty years now, and its tremendous pressure on the Socialist government has been exacerbated by the COVID-19 pandemic and hurricane Ian. One ought to ask the question, then, how Cuba remains so resilient after the collapse of the USSR. Although not a conclusive reason as to why Socialism remains prevalent in Cuba, this essay looks at one aspect of this new Cuban Socialism and its successes -- that being its farming systems. By looking at the roles polycultural cropping and alternative incentive schemes play in Cuba, I conclude that they both play a vital role in the development and reinforcement of Socialism in the island nation.